(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The purpose of this study was to determine the carbohydrate content in topinambur plants during the growing season, which were harvested in the Chui Valley at the experimental site of the Institute of Chemistry and fjtotechnology NAS KR in the village of Jany-Jer varieties “Nakhodka”. For the content of carbohydrates, the chemical composition was studied according to the phases of development. Apply the methods of paper chromatography, gel chromatography and the Kolthofg method.